Socioecological Mapping of Barriers and Enablers to Smoking Cessation in Indigenous Australian Women During Pregnancy and Postpartum: A Systematic Review. Issue 6 (11th January 2021) - Rahman, Tabassum; Eftekhari, Parivash; Bovill, Michelle; Baker, Amanda L; Gould, Gillian S
Abstract: Background: With a high prevalence of smoking during pregnancy and limited Indigenous-specific evidence for treatment, we used socioecological mapping to identify multilevel barriers and enablers to smoking cessation related to Indigenous Australian pregnant and postpartum women. Methods: Nine electronic databases were searched. Original studies except interventions and trials, published in English, up to February 29, 2020 were included. Studies were appraised using the QualSyst tool. Evidence was narratively synthesized. The review protocol was registered with PROSPERO (CRD42019135543). Results: A total of 15 studies (10 quantitative, 5 qualitative) were included, covering 1306 women, 3 partners/family members, 234 health professionals (HP), and 2755 patient records. Complex and overlapping barriers were identified at individual, family, community, societal, and system levels. Socioeconomic disadvantages, inequality, and pervasive racism as legacies of colonization, combined with personal, family, and community circumstances intensified individual experiences of stress, which may be heightened during pregnancy. Inadequate smoking cessation care (SCC), inconsistent antitobacco messages, and ineffectual HP interventions underscore a need for service enhancement and further evidence to develop culturally relevant messages. High motivation of pregnant women to quit, resilience, and supports available in the family and community are strengths that warrant attention in future interventions. Conclusions: SCC without ameliorating the social disadvantages and the disparities in health determinants between Indigenous and non-Indigenous Australian women may limit the effectiveness of SCC. A comprehensive approach is required that includes policy changes for addressing external stressors the women experience, engagement of family and community, and better training of HP and provision of free pharmacotherapy. Implications: To systematically address barriers to smoking cessation at multiple levels, initiatives to ameliorate social disadvantages and discrepancies in social determinants of health between Indigenous and non-Indigenous Australians are required to be taken in tandem with SCC. Initiatives may include making relevant policy changes and allocating more resources for education, employment, housing, and community development. Enhancement of knowledge, skills, and confidence of HP regarding the provision of high-quality SCC for Indigenous women and their families is warranted. Future interventions may build on high motivation, resilience, and strengths of individual women, and incorporate support strategies engaging family and community.